Association between maternal experiences of intimate partner violence and child stunting: a secondary analysis of the Demographic Health Surveys of four South Asian countries - Maryam Pyar Ali Lakhdir; Romaina Iqbal; Iqbal Azam; Bilal Ahmed Usmani; Muhammad Asim; Sobia Ambreen; Sonia Sameen; Saila Batool (BMJ Open)
Objectives To determine the association between maternal exposure to intimate partner violence (IPV) and child stunting using the Demographic Health Survey (DHS) data comparing four South Asian countries.Design A secondary analysis.Setting Data from the seventh round of the DHS data of four South Asian countries; Pakistan, Nepal, India and Maldives.Participants Married women of reproductive age (15–49 years) from each household were randomly selected, having at least one child less than 5 years of age for whom all anthropometric measures were available.Outcome measure The exposure variable was maternal IPV including, sexual violence, physical violence or both. The outcome variable was moderate or severe stunting, measured based on the height-for-age Z-score of children aged 6–59 months old . Multiple Cox proportional regression analyses were used separately on each country’s data to determine the association between maternal IPV and child stunting.Results The prevalence of IPV among women ranged from 10.17% in the Maldives to 31% in India. The burden of child stunting was the lowest in the Maldives at 14.04% and the highest in Pakistan at 35.86%. The number of severely stunted children was the highest in Pakistan (16.60%), followed by India (14.79%). In India, children whose mothers were exposed to IPV showed a 7% increase in the prevalence of moderate to severe child stunting (OR 1.07; 95% CI 1.01 to 1.14). Additionally, in Nepal, severe stunting was strongly associated with the prevalence of physical IPV (OR 1.66; 95% CI 1.01 to 2.87).Conclusion Our study findings suggest that maternal exposure to IPV is associated with child stunting. Further research investigating the relationship between IPV and child outcomes using improved and advanced statistical analyses can provide substantial evidence to enhance public awareness and potentially reduce the burden of child stunting in South Asian countries.